Numeracy Skills and Self-Confidence from the Perspective of Indonesian Students: A Systematic Literature Review - M. Rosyadi; Novaliyosi; Nindiasari, Hepsi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
The numeracy skills and self-confidence of students are two important and interrelated aspects in the mathematics learning process. This study aims to examine numeracy skills and self-confidence from the perspective of students. The method used is a systematic literature review (SLR), analyzing and selecting articles related to numeracy skills and self-confidence in mathematics education over the past five years (2019–2023) from the Google Scholar database. The review process followed the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) principles, with the aid of Publish or Perish (PoP) software. The results of this systematic literature review are: 1) There has been a positive trend in article publications over the last five years, with the highest number of publications in 2023, totaling 13 articles; 2) Numeracy skills, particularly from the perspective of initial abilities, were the most frequently discussed topic, found in 7 articles; 3) Self-confidence, from the perspective of student participation in the learning process, was the most common finding in 5 articles. Based on these results, it can be concluded that numeracy skills are crucial for the 21st century, and self-confidence is an essential skill needed by students to support their learning process.